Treating Public Health Dilemma of Gingival Recession by the Dehydrated Amnion Allograft: A 5-Year Longitudinal Study - Kumar, Santosh; Hirani, Tanvi; Shah, Sujay; Mehta, Rupal; Bhakkand, Susmita R.; Shishoo, Deepak (Frontiers in Oral Health, 2020)
Aim: This study aimed to evaluate the efficacy of dehydrated amnion allograft with coronally positioned flap procedure in paired Millers class I recession defects. Methods: Total of 51 subjects were included in the study with bilateral Miller’s class 1 gingival recession defects. In the test group, patients were treated with an amniotic membrane with a coronally positioned flap while in the control group, patients were treated with coronally positioned flap alone. Clinical Parameters such as Recession Depth, Recession width, Probing depth, Relative attachment level, Width of keratinised gingiva and Thickness of keratinised gingiva were recorded at baseline and after five years of follow up. Result: The mean baseline recession was 2.95±0.89 in test group whereas 2.70±0.85 in control group and both were statically non-significant. At the end of 6 months, all the parameters, when compared with the baseline, showed a significant improvement. Intergroup comparison showed the non-significant difference in all settings except the thickness of keratinised gingiva (TKG). Conclusion: Amniotic membrane proved to help improve the thickness of keratinised gingiva. This increase in thickness helps in the long-term maintenance of the gingival margin in Miller's class I recession defect.